2020
DOI: 10.1186/s12866-020-01760-4
|View full text |Cite
|
Sign up to set email alerts
|

Difference in virulence between Neisseria meningitidis serogroups W and Y in transgenic mice

Abstract: Background: Neisseria meningitidis serogroups W and Y are the most common serogroups causing invasive meningococcal disease in Sweden. The majority of cases are caused by the serogroup W UK 2013 strain of clonal complex (cc) 11, and subtype 1 of the serogroup Y, YI strain of cc23. In this study, virulence factors of several lineages within cc11 and cc23 were investigated in transgenic BALB/c mice expressing human transferrin. Transgenic mice were infected intraperitoneally with serogroup W and Y isolates. Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(49 reference statements)
2
4
0
Order By: Relevance
“…It is not known why this strain rarely infects children. The higher mortality rates in Sweden for MenW infections (14%) compared with MenY infections (9%) [4] are consistent with studies on a mouse model expressing human transferrin infected with these isolates, in which MenW isolates induced higher bacteraemia levels and proinflammatory activity as well as a higher degree of apoptosis [23].…”
Section: Discussionsupporting
confidence: 82%
“…It is not known why this strain rarely infects children. The higher mortality rates in Sweden for MenW infections (14%) compared with MenY infections (9%) [4] are consistent with studies on a mouse model expressing human transferrin infected with these isolates, in which MenW isolates induced higher bacteraemia levels and proinflammatory activity as well as a higher degree of apoptosis [23].…”
Section: Discussionsupporting
confidence: 82%
“…Many studies, dating from the 1970s, demonstrate the importance of iron acquisition in meningococcal disease [ 32 ], exemplified by the presence of multiple meningococcal ATP-dependent iron acquisition systems including transferrin binding proteins (TbpAB), lactoferrin binding proteins (LbpAB), and hemoglobin (HmbR) and hapto-hemoglobin receptors (HpuAB). One study using transgenic mice expressing human transferrin found amino acid substitutions were observed in several iron acquisition genes that were associated with differences in virulence capacity in mice between meningococci belonging to cc11 and cc23 [ 33 ]. In other studies of transgenic mice expressing human transferrin, tbpB mutants were cleared significantly more rapidly than wild-type meningococci [ 34 ], and in human experimental infection models, tbpA/tbpB deletion mutants of the closely related species Neisseria gonorrhoeae did not cause disease [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only one carriage isolate was grouped as MenW, belonging to the MenW cc11 2013 strain. The high incidence of MenW cc11 2013 strain invasive infections in Sweden may be due to high bacterial virulence, as studies on transgenic mice have shown that isolates of this particular strain caused higher levels of bacteraemia and induced more proinflammatory activity compared to MenY cc23 isolates [ 35 ]. Meningococcal carriage may induce bactericidal antibodies that are mainly strain-specific and would therefore not induce a general humoral defence against diverse meningococcal strains [ 36 ].…”
Section: Discussionmentioning
confidence: 99%